Pemahaman Ekonomi Islam Pada Usia Sekolah Di Lingkungan Masjid Luar Batang Penjaringan Jakarta Utara - tatik mariyanti (LPPM Universitas Putera Batam, 2020)
The purpose of this Join Community Service (PKM) with Faculty of Economy and Business Trisakti University and Faculty OF Economy and Business Esa Unggul University activity is to increase understanding of the Islamic economy and Islamic financial and banking institutions for school-aged children in environment of Masjid Luar Batang, Jakarta Indonesia. The method used is a survey and observation method with descriptive analysis from previous literature studies. The survey and observation methods were carried out by conducting direct outreach socialisation by presenting speakers and extension workers to school age. The material provided by giving an explanation of Islamic economics and the mechanism of Islamic financial institutions and banking. The next activity is evaluating the extension activities with interactions during the counseling session, such as questions and answers where questions from the instructor can be answered properly. Understanding of Islamic economics in school-age children in environment of Masjid Luar Batang has increased, but support from industry and the government is expected to be able to produce human resources that are reliable and can compete at the international level.